2019
DOI: 10.1126/science.aau0099
|View full text |Cite
|
Sign up to set email alerts
|

Males as somatic investment in a parthenogenetic nematode

Abstract: We report the reproductive strategy of the nematode Mesorhabditis belari. This species produces only 9% males, whose sperm is necessary to fertilize and activate the eggs. However, most of the fertilized eggs develop without using the sperm DNA and produce female individuals. Only in 9% of eggs is the male DNA utilized, producing sons. We found that mixing of parental genomes only gives rise to males because the Y-bearing sperm of males are much more competent than the X-bearing sperm for penetrating the eggs.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…We previously showed that M. belari females are unable to mate with males from three other Mesorhabditis species, including two standard sexual species. M. belari is thus auto-pseudogamous, a reproductive strategy that we showed to be evolutionary stable [5]. The fact that amphimictic eggs always give rise to males is explained by the fact that although sex determination is through a XY system, an almost complete Y-bearing sperm drive occurs at fertilization [5].…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…We previously showed that M. belari females are unable to mate with males from three other Mesorhabditis species, including two standard sexual species. M. belari is thus auto-pseudogamous, a reproductive strategy that we showed to be evolutionary stable [5]. The fact that amphimictic eggs always give rise to males is explained by the fact that although sex determination is through a XY system, an almost complete Y-bearing sperm drive occurs at fertilization [5].…”
Section: Introductionmentioning
confidence: 61%
“…This reproductive system, although rare, has been described in several plant and animal taxa, including vertebrates [3,4]. In the nematode Mesorhabditis belari, a special type of pseudogamy is found, which we call auto-pseudogamy, where, as a source of sperm, females produce their own males at low frequency [5,6]. Populations of M. belari are thus mainly composed of females but also of a lower frequency of males (9% in strain JU2817).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generating males at a low frequency can theoretically aid the spread and maintenance of gynogenesis by transmitting alleles required for diploid maternal inheritance into neighboring sexual populations [53]. The production of males even at a low frequency can also help propagate an intraspecific gynogenetic lineage by enabling the activation of the egg and inheritance of centrioles without relying on males from a related species, as seen in Mesorhabditis belari [54]. Thus, it is notable that gynogenetic reproduction in C. nouraguensis x C. becei hybridizations already exhibits the ability to produce males.…”
Section: Characteristics Of Incipient Gynogenesismentioning
confidence: 99%
“…Variation in mating systems is especially familiar in plants, but has also been one of the longstanding attractions of nematode biology (Nigon & Félix, 2017) . Just within Rhabditidae, this aspect of life-history now spans systems with separate males and females (gonochorism), males and self-fertile hermaphrodites (androdioecy; Kanzaki et al, 2017;Mayer et al, 2007) , males, females, and hermaphrodites (trioecy; Chaudhuri et al, 2015;Kanzaki et al, 2017) , asexual reproduction where sperm does not contribute genetic material (parthenogenesis, gynogenesis; Fradin et al, 2017;Grosmaire et al, 2019) , and alternating generations of hermaphroditism and dioecy (heterogony; Kiontke, 2005) .…”
Section: Introductionmentioning
confidence: 99%